2022
DOI: 10.14254/2071-789x.2022/15-4/6
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial competencies of university students

Abstract: Entrepreneurial competencies have become a tool that can be learned. Education encourages the entrepreneurial way of thinking at the individual level, and thus develops the societal outlook. Various EU funds and non-profit organizations support initiatives for the development of entrepreneurial competencies and educating young people as this has been recognized as an important element of building a global society. This research was conducted through an online survey at two private universities, Singidunum in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The results presented in this paper represent the first empirical evidence on the level of university students DEC for the specified competence area, using the EmDigital framework. In line with findings on the relationship between DEC and DEI [ 26 , 27 ] and studies that assessed EC of university students [ 35 ] and examined the relationship between levels of EC and various socio-demographic characteristics of university students [ 36 ] to examine the success of university-level entrepreneurship education in creating EC as a critical determinant in building students' EI, this study contributes to the assessment of DEC and associating their levels with various socio-demographic characteristics of university students (as suggested by Alferaih [ 26 ]) to investigate the success of university-level digital entrepreneurship education in creating DEC. Moreover, this study responds to a call for future research aimed at creating entrepreneurial competences in the Digital “University based” Entrepreneurial ecosystems proposed by Secundo et al [ 40 ].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The results presented in this paper represent the first empirical evidence on the level of university students DEC for the specified competence area, using the EmDigital framework. In line with findings on the relationship between DEC and DEI [ 26 , 27 ] and studies that assessed EC of university students [ 35 ] and examined the relationship between levels of EC and various socio-demographic characteristics of university students [ 36 ] to examine the success of university-level entrepreneurship education in creating EC as a critical determinant in building students' EI, this study contributes to the assessment of DEC and associating their levels with various socio-demographic characteristics of university students (as suggested by Alferaih [ 26 ]) to investigate the success of university-level digital entrepreneurship education in creating DEC. Moreover, this study responds to a call for future research aimed at creating entrepreneurial competences in the Digital “University based” Entrepreneurial ecosystems proposed by Secundo et al [ 40 ].…”
Section: Discussionsupporting
confidence: 74%
“…These findings are consistent with a large number of studies that have shown that “traditional” entrepreneurship education programmes aimed at developing the entrepreneurial competences (EC) of university students have an impact on their entrepreneurial intention (EI) [ [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. Given the positive relationship between EC and EI, empirical studies have been conducted to assess the level of EC of university students [ 35 ] and to relate the level of EC with various socio-demographic characteristics of university students [ 36 ]. The main purpose of these studies was to investigate the success of university entrepreneurship education in creating EC as a crucial determinant for the development of students' EI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation